European Pharmacy Students' Experience With Virtual Patient Technology - Cavaco, Afonso Miguel (2015)
Objective. To describe how virtual patients are being used to simulate real-life clinical scenarios in undergraduate pharmacy education in Europe. Methods. One hundred ninety-four participants at the 2011 Congress of the European Pharmaceutical Students Association (EPSA) completed an exploratory cross-sectional survey instrument. Results. Of the 46 universities and 23 countries represented at the EPSA Congress, only 12 students from 6 universities in 6 different countries reported having experience with virtual patient technology. The students were satisfied with the virtual patient technology and considered it more useful as a teaching and learning tool than an assessment tool. Respondents who had not used virtual patient technology expressed support regarding its potential benefits in pharmacy education. French and Dutch students were significantly less interested in virtual patient technology than were their counterparts from other European countries. Conclusion. The limited use of virtual patients in pharmacy education in Europe suggests the need for initiatives to increase the use of virtual patient technology and the benefits of computer-assisted learning in pharmacy education.